2017
DOI: 10.1186/s40463-017-0206-2
|View full text |Cite
|
Sign up to set email alerts
|

Surgical site infections following oral cavity cancer resection and reconstruction is a risk factor for plate exposure

Abstract: BackgroundPlate-related complications following head and neck cancer ablation and reconstruction remains a challenging problem often requiring further management and reconstructive surgeries. We aim to identify an association between surgical site infections (SSI) and plate exposure.MethodsA retrospective study between 1997 and 2014 was performed to study the association between postoperative SSI and plate exposures. Eligible patients included those with a history of oral squamous cell carcinoma who underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 45 publications
2
30
1
Order By: Relevance
“…Infections of the head and neck following ablative surgery may lead to bacterial colonization of plates, resulting in biofilm formation, wound contamination, and subsequent plate exposure requiring hardware removal to eliminate the nidus of infection. [9] Persistent infection was not controlled by all types of higher antibiotics in this case.…”
Section: Infectionsmentioning
confidence: 64%
See 2 more Smart Citations
“…Infections of the head and neck following ablative surgery may lead to bacterial colonization of plates, resulting in biofilm formation, wound contamination, and subsequent plate exposure requiring hardware removal to eliminate the nidus of infection. [9] Persistent infection was not controlled by all types of higher antibiotics in this case.…”
Section: Infectionsmentioning
confidence: 64%
“…This is likely due to the length of the plate in addition to the associated soft-tissue defects. [9] In the present case, mandibulectomy was performed.…”
Section: Extent Of Mandibular Resectionmentioning
confidence: 81%
See 1 more Smart Citation
“…According to the literature, surgical site infections (SSIs) following head and neck cancer surgery may occur in up to 10 to 45% of cases, despite antibiotic prophylaxis. [28] Yao et al [29] reported that 84 patients (23%) of 365 patients developed SSI within 30 days of the operation and the most common SSI formed were neck abscesses (11.5%). In the present study, we observed SSI in 31 patients (6.8%), which is much lower than similar studies.…”
Section: Discussionmentioning
confidence: 99%
“…HIV disease status was classified using world health organization (WHO) clinical stage classification 24 . SSI were defined as infections occurring within 30 days of the procedure, according to the CDC parameters 26 , 27 . TB screen in HIV/AIDS patients were conducted using the WHO-recommended symptom screen (cough, fever, night sweats, weight loss) 28 .…”
Section: Methodsmentioning
confidence: 99%